Method for producing industrial silicon and co-producing deoxidizer by precise gradient cooling and centrifugation of aluminum-silicon raw material

By accurately gradient cooling and centrifuging the aluminum-silicon raw materials, a silicon-aluminum-ferroalloy melt with a skeleton structure is formed. Through centrifugation and reselection separation technology, it is solved by difficult to control the furnace condition and low raw material utilization in the existing industrial silicon production methods. The problem of environmental pollution has achieved efficient and low-cost production of industrial silicon and iron-rich phase products.

CN119433190AInactive Publication Date: 2025-02-14JILIN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310976716.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing industrial silicon production methods have problems such as difficult to control the furnace conditions, low raw material utilization rate, high production costs, high power consumption, difficult to improve product quality, and negative impact on the environment, and the difficulty in separating and utilizing aluminum-silicon raw materials.

Method used

The production of industrial silicon is produced by precise gradient cooling centrifugation by controlling the cooling rate and insulation time. By controlling the cooling rate and insulation time, a silicon-aluminum-ferroalloy melt with a skeleton structure is formed, and solid-liquid separation is achieved through centrifugation. Finally, polysilicon and rich are obtained through reselection separation. Iron phase products.

Benefits of technology

Effective separation of silicon phase and iron phase is achieved, the purity and added value of industrial silicon are improved, production costs are reduced, environmental pollution is reduced, and resource utilization is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433190A_ABST
    Figure CN119433190A_ABST
Patent Text Reader

Abstract

The invention discloses a method for producing industrial silicon and co-producing a deoxidizing agent by precise gradient cooling and centrifugation of an aluminum-silicon raw material. According to the invention, by changing the cooling system, the ferro-silicon-aluminum melt obtained after the electric heating reduction of the silicon-aluminum raw material forms a silicon phase and iron phase grain interlaced skeleton structure with controllable size, morphology, phase composition and element composition in the gradient cooling or heat preservation process; therefore, after the aluminum-silicon alloy is centrifugally separated at high temperature, the residual solid silicon phase and iron phase grain interlaced skeleton structure can be simply crushed and reselected to realize the separation of polycrystalline silicon and iron phase. The process is completely different from a traditional silicon and aluminum production process, a pure silicon source and a pure aluminum source are not needed, production of industrial silicon can be achieved only by applying a silicon-aluminum raw material, meanwhile, a deoxidizing agent can be obtained, and the process has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of smelting technology, and in particular relates to a method for producing industrial silicon and co-producing a deoxidizer by accurately gradient cooling and centrifuging aluminum silicon raw materials. Background Art

[0002] Aluminum is an important basic material for traditional industries. With the vigorous development of modern industry, modern science and new technologies, silicon and silicon-containing materials have become increasingly important basic materials. Their applications have been popularized in various modern industrial fields such as automobiles, ships and aviation. Bauxite is an important source of aluminum in modern industry. However, my country's bauxite resources are small, and the supply of bauxite has been unable to meet domestic demand for a long time. In addition, although my country is rich in silicon ore resources, with the rapid development of the industrial silicon industry and the need for environmental protection, the available resources have also been sharply reduced. Industrial silicon is mainly prepared by electrothermal reduction smelting, that is, silica and carbon reducing agent are crushed to a certain particle size, mixed and put into the ore heat for smelting, in which the reducing agent used is mainly wood blocks, and a certain amount of petroleum coke and washed coal are added. In the production process of this method, the furnace condition is easy to fluctuate and difficult to control, and the raw material utilization rate is low, the production cost is high, the power consumption is high, the product quality is difficult to improve, the smoke and dust emissions are large, and the impact on the surrounding environment is relatively large. In addition, wood blocks need to be added during the smelting process, which will consume a large amount of forest resources and cause damage to the ecological environment.

[0003] Therefore, it is of great economic significance to find alternative aluminum silicon raw material resources. In fact, my country has many types of aluminum silicon raw materials and rich reserves. In addition to bauxite, clay, kyanite, fly ash, coal gangue, etc. are all aluminum silicon raw materials with high aluminum silicon content, especially fly ash and coal gangue. Because the aluminum and silicon in them are difficult to separate, they are usually difficult to be used to produce aluminum silicon products. Chinese patent CN202011267925.4 provides a method for preparing aluminum silicon iron alloy using high aluminum fly ash and graded purification. Chinese patent CN202011267903.8 provides a method for preparing aluminum silicon iron alloy using high aluminum coal gangue and graded purification. Both patent documents mention the method of preparing aluminum silicon iron alloy blocks and graded purification to obtain aluminum silicon iron alloy for deoxidizer. Chinese patent CN202011266119.5 provides a method for extracting industrial silicon from aluminum-silicon-ferroalloy, which can simultaneously obtain aluminum-silicon-ferroalloy for deoxidizer and industrial silicon. However, the industrial silicon obtained by this method has a high iron content and is still difficult to use.

[0004] The present invention attempts to improve the methods based on the above patent documents. Summary of the invention

[0005] The purpose of the present invention is to improve the patented technology mentioned in the background technology, and obtain a method for producing industrial silicon co-production deoxidizer by precise gradient cooling and centrifugation of aluminum silicon raw materials. The technical solution adopted by the present invention to solve its technical problems is:

[0006] A method for producing industrial silicon and co-producing deoxidizer by centrifugation of aluminum-silicon raw materials with precise gradient cooling, comprising the following steps:

[0007] (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt;

[0008] (2) Under controlled cooling conditions, the obtained aluminum-silicon-iron melt is subjected to gradient cooling, wherein the gradient cooling includes two or more stages in the following temperature control stages: in the first stage, the temperature is reduced to 800-1300° C. at a cooling rate of 1-20° C. / min and kept warm for 10-200 min; in the second stage, the temperature is reduced to 650-1000° C. at a cooling rate of 0.1-20° C. / min and kept warm for 10-200 min; in the third stage, the temperature is reduced to 600-850° C. at a cooling rate of 0.1-20° C. / min and kept warm for 10-200 min; in the fourth stage, the temperature is reduced to 570-650° C. at a cooling rate of 0.1-20° C. / min to obtain a silicon-aluminum-iron alloy melt with a skeleton structure;

[0009] (3) centrifuging the obtained silicon-aluminum-iron alloy melt having a skeleton structure to achieve solid-liquid separation, wherein the solid state is maintained as an interwoven skeleton structure formed by the growth of silicon phase and iron phase;

[0010] (4) crushing and sieving the solid porous interwoven skeleton structure sample composed of silicon phase and iron phase skeleton obtained in the previous step to 40-200 mesh;

[0011] (5) The sieved samples obtained in the previous step are subjected to gravity separation to achieve separation of silicon phase and iron phase. The small density samples are collected as polycrystalline silicon products, which are directly used as industrial silicon for producing solar-grade polycrystalline silicon; the large density samples are iron-rich phase grains, which are directly used as deoxidizers in industries such as steelmaking and magnesium smelting.

[0012] After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.

[0013] Preferably, the gradient cooling in step (2) comprises: in the first stage, cooling to 850-1150°C at a cooling rate of 5-15°C / min, and keeping warm for 20-60min; in the second stage, cooling to 700-900°C at a cooling rate of 0.5-10°C / min, and keeping warm for 20-60min; in the third stage, cooling to 600-750°C at a cooling rate of 0.5-10°C / min, and keeping warm for 20-60min; in the fourth stage, cooling to 577-650°C at a cooling rate of 0.5-10°C / min.

[0014] Preferably, in step (3), the obtained melt is first heated to 577-700° C., kept warm for 0-360 min, and then centrifuged.

[0015] After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.

[0016] The gravity separation described in step (5) can be carried out by using a cyclone chute to separate the crushed sample in step (4) into a 2-40% slurry. After separation, the collected samples with low density are polycrystalline silicon, while the samples with high density are iron-rich phases.

[0017] The gravity separation described in step (5) can be separated by a shaking table to prepare a slurry of about 2-70%. After separation, the collected samples with low density are polycrystalline silicon, and the samples with high density are iron-rich phases.

[0018] The gravity separation described in step (5) can be separated by a two-product heavy medium cyclone. The solid-liquid ratio of the sample to the heavy medium suspension after screening is 1:2.5-1:4.5, the volume concentration of the heavy medium suspension is 15%-30%, and the heavy medium suspension is composed of one or more of sodium polytungstate, calcium bromide, zinc bromide or calcium iodide. After sorting, the collected sample with low density is polysilicon; the sample with high density is iron-rich phase.

[0019] In the above method, the silicon-alumina raw material in step (1) can be one or a mixture of natural silicon-alumina minerals, solid waste containing silicon-alumina, or artificially synthesized silicon-alumina raw materials, wherein the natural silicon-alumina minerals include bauxite, kaolinite, albite, potassium feldspar, etc., and the solid waste containing silicon-alumina includes bauxite flotation tailings, coal gangue, fly ash, shale slag, etc.

[0020] In the above method, the carbonaceous reducing agent in step (1) includes coal, petroleum coke, calcined anthracite, coke, metallurgical coke, one of which or a mixture of several thereof.

[0021] In the above method, the amount of the carbonaceous reducing agent in step (1) is 90-95% of the required reducing agent. If it exceeds 95%, the metal carbides (especially aluminum carbide) in the alloy will increase, which will not only reduce the alloy yield but also affect the stability of arc furnace smelting.

[0022] In the above method, the mass of the binder added in step (1) is 5-10% of the mixed material, the pelletizing pressure is 50-150 MPa, the pellet drying temperature is 150-200°C, and the moisture content of the pellets after drying is not more than 1%.

[0023] In the above method, the reduction reaction temperature in the electric arc furnace in step (1) is 2200-2500°C.

[0024] In the above method, the interwoven skeleton structure described in step (2) is a skeleton structure constructed by silicon grains and iron phase grains, which still retains the macroscopic structure of the aluminum-silicon-iron alloy described in step (1) to a certain extent in appearance after centrifugal treatment, but is loose and porous inside; the gaps in the skeleton structure are filled with aluminum-silicon alloy similar to a binder.

[0025] In the above method, the silicon phase in the interwoven skeleton structure is mainly composed of silicon element.

[0026] In the above method, the Fe mass content of the iron phase in the interwoven skeleton structure is 9.7-65%, the Al mass content is 10-68%, and the Si mass content is 12-30%.

[0027] In the above method, the physical composition of the iron phase in the interwoven skeleton structure is mainly one or more of Al4FeSi, Al3FeSi2, Al2Fe5Si5, Al9Fe5Si5, and Al3Fe3Si2.

[0028] In the above method, the crushing described in step (4) can be carried out by a hammer crusher, a jaw crusher, a disc crusher, a double-roll crusher, etc., and the mesh size requirement can be achieved through a cyclic crushing method.

[0029] The cooling mechanism of the present invention is:

[0030] When the melt is cooled, solidification phases gradually precipitate from the material, and the following steps are performed:

[0031] L→Si

[0032] L→Si+Al3FeSi2

[0033] L+Al3FeSi2→Al4FeSi+Si

[0034] L→Al+Si+Al4FeSi

[0035] First, in the primary crystallization zone of silicon, when the melt begins to cool down, the elemental Si phase will precipitate first as the temperature continues to drop; then, after entering the iron-rich phase zone, Al3FeSi2 also begins to precipitate; when the temperature continues to drop, there will be a melting process, that is, the phase and the remaining liquid phase melt to form Al4FeSi phase and elemental silicon; finally, when the temperature reaches the low eutectic point temperature of the system, the liquid phase will completely solidify and precipitate as elemental aluminum, elemental silicon and Al4FeSi phase.

[0036] According to the ratio of aluminum, silicon and iron elements in the raw materials, the cooling and condensation process is different. In particular, when the melt cooling mechanism is precisely controlled, the grain size of each solidified phase can be effectively controlled, so that the silicon phase and iron-rich phase with larger grain size can be obtained after full growth, which provides the possibility for the effective separation of the subsequent silicon phase and iron phase. At the same time, by adjusting the holding time and cooling rate of each temperature zone, the content ratio of the iron-rich phase Al3FeSi2 and Al4FeSi phase can be effectively adjusted to increase the content of the iron-rich phase Al3FeSi2 in the final solid phase. Due to the obvious difference in the morphology of the iron-rich phase Al3FeSi2 and Al4FeSi grains, the Al3FeSi2 phase is more likely to grow into coarse grains, while the opposite phase Al4FeSi phase tends to grow into fine needles. Needle-shaped grains are very easy to break into smaller particles during the subsequent separation of silicon phase and iron phase, which makes it impossible to separate the two phases through the density difference between the iron phase and the silicon phase, and it is impossible to effectively obtain high value-added single silicon products. However, when the iron-rich phase Al3FeSi2 is dominant in the product, phase separation can be effectively achieved by controlling the large-particle iron-rich phase and silicon phase and utilizing the density difference between the two phases.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. During the cooling and crystallization process of the aluminum-silicon-iron melt, the silicon phase precipitates and grows at high temperature; as the temperature decreases, the iron phase begins to precipitate and interweaves with the silicon phase to form a unique skeleton structure; as the temperature continues to drop, the remaining aluminum-silicon alloy melt solidifies and exists in the skeleton gaps formed by the silicon phase and the iron phase to form a solid block;

[0039] 2. In the process of forming the interwoven framework of silicon phase and iron phase, the aluminum silicon iron melt is gradually cooled or kept warm by precisely controlling the cooling mechanism, so as to control the size, morphology, phase composition and element composition of the crystal morphology of silicon phase and iron phase and the internal organizational structure of the alloy;

[0040] 3. During the cooling process of the aluminum-silicon-ferrosilicon melt, the silicon phase first precipitates at high temperature. By controlling the cooling rate, insulation temperature and time, the silicon phase gradually grows to a suitable size, which is more conducive to subsequent separation and extraction;

[0041] 4. According to the ratio of aluminum, silicon and iron in the raw materials, a suitable temperature zone is selected for heat preservation or gradient cooling, and the appropriate heat preservation time and cooling rate are matched to effectively realize the regulation of the phase composition of the iron phase. The precipitated iron phase can be one or more of Al4FeSi, Al3FeSi2, Al2Fe5Si5, Al9Fe5Si5, and Al3Fe3Si2; and through the adjustment of the cooling process, the particle size and growth morphology of the iron phase can be effectively regulated during the transformation of different crystal phases, providing favorable conditions for the subsequent separation of silicon phase and iron phase;

[0042] 5. After strict temperature reduction control, the iron phase can grow into large-sized grains, and effectively improve the previous needle-shaped growth orientation, making it possible to separate silicon and iron. Combined with the density difference between the silicon phase and the iron phase, polysilicon products and iron-rich phase products can be obtained by gravity separation methods such as cyclone troughs and shaking tables. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a photo of the cast aluminum-silicon alloy obtained in Example 1.

[0044] Figure 2 The solid remaining after centrifugation obtained in Example 1.

[0045] Figure 3 This is a partial enlarged photograph of the solid remaining after centrifugation obtained in Example 1. DETAILED DESCRIPTION

[0046] The following is a detailed description of an embodiment of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0047] Example 1

[0048] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 43.78%, the mass fraction of SiO2 is 50.15%, and the mass fraction of Fe2O3 is 1.69%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine at a pelletizing pressure of 100MPa, dry and dehydrate the prepared pellets at 120℃ to obtain dry lumps, with a moisture content of no more than 1%, and then put the dry lumps into an electric arc furnace for reduction reaction, with a smelting temperature of 2200-2500℃. When the molten aluminum silicon iron alloy melt is cooled to 1400℃, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 1000℃ at 10℃ / min; keeping at 1000℃ for 30min; cooling to 800℃ at 1.5℃ / min; cooling to 700℃ at 10℃ / min; keeping at 700℃ for 30min; cooling to 600℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into the hanging basket, and the centrifuge was started at 600°C, the super gravity coefficient was 200g, and the separation time was 180min. The melt was separated by a porous filter plate, and the melt was cooled and solidified to obtain a cast aluminum-silicon alloy that meets industrial standards (such as Figure 1 As shown), the mass fraction of Fe is 0.87% and the mass fraction of Si is 12.78%.

[0049] The solid sample remaining in the basket after centrifugation (such as Figure 2 The appearance of the aluminum-silicon-iron alloy still maintains the macroscopic structure to a certain extent, but the interior is loose and porous (such as Figure 3 As shown in the figure, the sample to be separated is crushed by a hammer crusher, and the sample of 120-200 mesh is obtained by screening. The slurry is prepared into about 10% slurry by using a rotary chute for sorting. According to the color of the fan-shaped surface formed by the slurry falling in the selection chute, the scraper position is adjusted to collect the slurry with a smaller density (outer circle), which is the polysilicon sample. After a simple dilute acid treatment and washing away a small amount of residual aluminum, the polysilicon product is obtained with a purity of 99.0%. The remaining product after silicon extraction is a deoxidizer product mainly composed of an iron-rich phase.

[0050] The above process can obtain 50.75kg of cast silicon aluminum alloy, 23.34kg of polysilicon product, and 25.12kg of deoxidizer product per 100kg of melt, and the specific product conditions are shown in Table 1. Table 1 shows the mass of each product obtained in Examples 1-4 and the content of some elements.

[0051] Example 2

[0052] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 42.96%, the mass fraction of SiO2 is 51.07%, and the mass fraction of Fe2O3 is 1.54%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine, and the pelletizing press is used. The pressure is 100MPa, and the prepared pellets are dried and dehydrated at 120℃ to obtain dry lumps, with a moisture content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction, with a smelting temperature of 2200-2500℃. When the molten aluminum silicon iron alloy melt is cooled to 1400℃, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 900℃ at 10℃ / min; keeping at 900℃ for 30min; cooling to 750℃ at 1℃ / min; cooling to 700℃ at 10℃ / min; keeping at 700℃ for 30min; cooling to 650℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into a hanging basket, placed in an ultragravity centrifuge equipped with a heating device, and the centrifuge was started at 650°C. The ultragravity coefficient was 200g, the separation time was 180min, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 0.89% and the Si mass fraction was 12.85%.

[0053] The solid sample remaining in the basket after centrifugation still maintains the macroscopic structure of aluminum-silicon-iron alloy to a certain extent in appearance, but the inside is loose and porous. The sample to be separated is crushed by a hammer crusher and sieved to obtain a sample of 120-200 mesh. The slurry is prepared into about 10% slurry by using a rotary chute for sorting. According to the color of the fan-shaped surface formed by the slurry falling in the selection chute, the scraper position is adjusted to collect the slurry with a smaller density (outer circle), which is the polysilicon sample. After a simple dilute acid treatment and washing away a small amount of residual aluminum, the polysilicon product is obtained with a purity of 99.1%. The remaining product after silicon extraction is a deoxidizer product mainly composed of iron-rich phase.

[0054] The above process can obtain 48.60kg of cast silicon aluminum alloy, 24.89kg of polysilicon product, and 16.53kg of deoxidizer product for every 100kg of melt. The specific product conditions are shown in Table 1.

[0055] Example 3

[0056] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.75 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 43.25%, the mass fraction of SiO2 is 47.56%, and the mass fraction of Fe2O3 is 4.45%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the mixed material, and then the mixed material is made into a briquette machine. The pellets are formed at a pressure of 100 MPa. The prepared pellets are dried and dehydrated at 120°C to obtain dry lumps, with a water content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500°C. When the molten aluminum silicon iron alloy is cooled to 1400°C, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 950°C at 10°C / min; keeping at 950°C for 30min; cooling to 850°C at 1°C / min; keeping at 850°C for 30min; cooling to 600°C at 2°C / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into a hanging basket, placed in an ultragravity centrifuge equipped with a heating device, and the centrifuge was started at 600°C. The ultragravity coefficient was 200g, the separation time was 180min, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 0.82% and the Si mass fraction was 11.96%.

[0057] The solid sample remaining in the basket after centrifugation still maintains the macroscopic structure of aluminum-silicon-iron alloy to a certain extent in appearance, but the inside is loose and porous. The sample to be separated is crushed by a hammer crusher and sieved to obtain a sample of 120-200 mesh. The slurry is prepared into about 10% slurry by using a rotary chute for sorting. According to the color of the fan-shaped surface formed by the slurry falling in the selection chute, the scraper position is adjusted to collect the slurry with a smaller density (outer circle), which is the polysilicon sample. After a simple dilute acid treatment and washing away a small amount of residual aluminum, the polysilicon product is obtained with a purity of 98.5%. After extracting silicon, the remaining product is a deoxidizer product mainly composed of iron-rich phase.

[0058] The above process can obtain 51.90kg of cast silicon aluminum alloy, 23.55kg of polysilicon product, and 24.37kg of deoxidizer product for every 100kg of melt. The specific product conditions are shown in Table 1.

[0059] Example 4

[0060] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.79 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 40.35%, the mass fraction of SiO2 is 45.89%, and the mass fraction of Fe2O3 is 8.22%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with sulfite pulp binder and 10% of water to mix the mixed material, and then the mixed material is placed in a briquetting machine. The pellets are made at a pressure of 100 MPa, and the prepared pellets are dried and dehydrated at 120°C to obtain dry lumps, with a water content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500°C. When the molten aluminum silicon iron alloy melt is cooled to 1400°C, it is cast in a mold and placed in a tunnel kiln for gradient temperature control. The gradient temperature control is carried out, cooling to 950°C at 10°C / min; cooling to 850°C at 1°C / min; cooling to 800°C at 10°C / min; and cooling to 650°C at 2°C / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into a hanging basket, placed in an ultragravity centrifuge equipped with a heating device, and the centrifuge was started at 650°C. The ultragravity coefficient was 200g, the separation time was 180min, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 1.45% and the Si mass fraction was 14.36%.

[0061] The solid sample remaining in the basket after centrifugation still maintains the macroscopic structure of aluminum-silicon-iron alloy to a certain extent in appearance, but the interior is loose and porous. The sample to be separated is crushed by a hammer crusher and sieved to obtain a sample of 120-200 mesh. The slurry is prepared into about 10% slurry by using a rotary chute for sorting. According to the color of the fan-shaped surface formed by the slurry falling in the selection chute, the scraper position is adjusted to collect the slurry with a smaller density (outer circle), which is the polysilicon sample. After a simple dilute acid treatment and washing away a small amount of residual aluminum, the polysilicon product is obtained with a purity of 98.6%. The remaining product after silicon extraction is a deoxidizer product mainly composed of an iron-rich phase.

[0062] The above process can obtain 49.31kg of cast silicon aluminum alloy, 25.01kg of polysilicon product, and 25.21kg of deoxidizer product for every 100kg of melt. The specific product conditions are shown in Table 1.

[0063] Table 1

[0064]

Claims

1. A method for producing industrial silicon and co-producing deoxidizer by precise gradient cooling and centrifugation of aluminum silicon raw materials, characterized in that: The steps include: (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt; (2) Under controlled cooling conditions, the obtained aluminum-silicon-iron melt is subjected to gradient cooling, wherein the gradient cooling includes two or more stages in the following temperature control stages: in the first stage, the temperature is reduced to 800-1300° C. at a cooling rate of 1-20° C. / min and kept warm for 10-200 min; in the second stage, the temperature is reduced to 650-1000° C. at a cooling rate of 0.1-20° C. / min and kept warm for 10-200 min; in the third stage, the temperature is reduced to 600-850° C. at a cooling rate of 0.1-20° C. / min and kept warm for 10-200 min; in the fourth stage, the temperature is reduced to 577-650° C. at a cooling rate of 0.1-20° C. / min to obtain a silicon-aluminum-iron alloy melt with a skeleton structure; (3) centrifuging the obtained silicon-aluminum-iron alloy melt having a skeleton structure to achieve solid-liquid separation, wherein the interwoven skeleton structure formed by the growth of silicon phase and iron phase remains in the solid state; (4) crushing and sieving the solid porous interwoven skeleton structure sample composed of silicon phase and iron phase skeleton obtained in the previous step to 40-200 mesh; (5) The sieved samples obtained in the previous step are subjected to gravity separation to achieve separation of silicon phase and iron phase. The small density samples are collected as polycrystalline silicon products, which are directly used as industrial silicon for producing solar-grade polycrystalline silicon; the large density samples are iron-rich phase grains, which are directly used as deoxidizers in industries such as steelmaking and magnesium smelting.

2. The method for producing industrial silicon and co-producing deoxidizer by centrifugation with precise gradient cooling of aluminum-silicon raw materials according to claim 1, characterized in that: After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.

3. The method for producing industrial silicon and co-producing deoxidizer by centrifugation with precise gradient cooling of aluminum silicon raw materials according to claim 1, characterized in that: The gradient cooling in step (2) includes: in the first stage, the temperature is lowered to 850-1150°C at a cooling rate of 5-15°C / min and kept at this temperature for 20-60min; in the second stage, the temperature is lowered to 700-900°C at a cooling rate of 0.5-10°C / min and kept at this temperature for 20-60min; in the third stage, the temperature is lowered to 600-750°C at a cooling rate of 0.5-10°C / min and kept at this temperature for 20-60min; in the fourth stage, the temperature is lowered to 577-650°C at a cooling rate of 0.5-10°C / min.

4. The method for producing industrial silicon and co-producing deoxidizer by centrifugation with precise gradient cooling of aluminum-silicon raw materials according to claim 1, characterized in that: In step (3), the obtained melt is first heated to 577-700°C, kept warm for 0-360 minutes, and then centrifuged.

5. The method for producing industrial silicon and co-producing deoxidizer by centrifugation with precise gradient cooling of aluminum-silicon raw materials according to claim 1, characterized in that: After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.

6. The method for producing industrial silicon and co-producing deoxidizer by centrifugation with precise gradient cooling of aluminum-silicon raw materials according to claim 1, characterized in that: The gravity separation described in step (5) is carried out by using a rotary chute to prepare a 2-40% slurry of the crushed sample in step (4), and the sample with a small density is collected after separation as polycrystalline silicon; The high-density samples are iron-rich phases.

7. The method for producing industrial silicon and co-producing deoxidizer by centrifugation with precise gradient cooling of aluminum-silicon raw materials according to claim 1, characterized in that: The gravity separation described in step (5) is separated by a shaking table and prepared into a slurry of about 2-70%. After sorting, the collected samples with low density are polycrystalline silicon; the samples with high density are iron-rich phase.

8. The method for producing industrial silicon and co-producing deoxidizer by centrifugation with precise gradient cooling of aluminum-silicon raw materials according to claim 1, characterized in that: The gravity separation described in step (5) adopts a two-product heavy medium cyclone for separation. The solid-liquid ratio of the sample to the heavy medium suspension after screening is 1:2.5-1:4.5, the volume concentration of the heavy medium suspension is 15%-30%, and the heavy medium suspension is composed of one or more of sodium polytungstate, calcium bromide, zinc bromide or calcium iodide. After sorting, the collected low-density sample is polycrystalline silicon; the high-density sample is an iron-rich phase.

Citation Information

Patent Citations

  • Method for preparing aluminum-silicon-iron alloy from high-aluminum coal gangue and conducting graded purification

    CN113913621A

  • Method for extracting industrial silicon from aluminum-silicon-iron alloy

    CN114477187A

  • A method for preparing aluminum-silicon-iron alloy using high-aluminum fly ash and grading purification

    CN114480855B